PROFILE OF SCIENCE TEACHERS’ ASSESSMENT LITERACY - Monica Prima Sari; Rahmah Evita Putri; Rani Oktavia (SEMESTA: Journal of Science Education and Teaching, 2020)
Assessment literacy is fundamental for teacher because it is related to decision making task which will then give impact to students’ future. Assessment literacy influences teachers’ routine practice of assessment in classroom. Without knowing the current assessment literacy among teachers, it is difficult to monitor or give relevant reinforcement to improve the quality of assessment practice. Therefore, this study is aimed to figure out the profile of science teachers’ assessment literacy through a 54-items questionnaire developed from Assessment Literacy Standard (ALS) from Michigan Assessment Consortium. The questionnaire consists of selected choice response and open-ended question. Fifteen secondary school science teachers voluntarily participated in this study which came from 9 school in West Sumatra. Then, data was analyzed with descriptive analysis technique. Our findings revealed that while most teachers agreed with the ideal condition of assessment practice stated in the questionnaire, most are not sure when it comes to analyzing data from assessment with statistic tools or taking the use of assessment result further to improve learning quality for both students and teacher themselves. Implication of these findings on the preparation program of science student teacher in Universitas Negeri Padang was discussed further.